A passive-active combined strategy for ultrafiltration membrane fouling control in continuous oily wastewater purification. (1st November 2022) - Ding, Junwen; Wang, Jinlong; Luo, Xinsheng; Xu, Daliang; Liu, Yatao; Li, Peijie; Li, Shirong; Wu, Rui; Gao, Xinlei; Liang, Heng
Highlights: A passive-active combined strategy for fouling control was developed. Achievement of enhanced surface properties and superhydrophilicity. The oil fouling tendency was greatly mitigated, especially oil cake fouling. Singlet oxygen contributed most to irreversible fouling removal in PMS cleaning. Abstract: Membrane-based technology has been confirmed as an effective way to treat emulsified oily wastewater, however, membrane fouling is still one of practical challenges in long-term operation. Herein, a novel passive-active combined strategy was proposed to control membrane fouling in continuous oily wastewater purification, where the δ-MnO2 decoration layer helped to reduce the total fouling ratio (passive strategy for fouling mitigation) and the catalytic cleaning effectively removed the irreversible oil fouling (active strategy for fouling removal). The functional membrane was prepared via in-situ modification, referred to as δ-MnO2 @TA-PES. The morphology, crystalline phase, chemical structure and surface properties of the membranes were systematically characterized. Compared with PES, the δ-MnO2 @TA-PES possessed superhydrophilicity, enhanced electronegativity and narrowed pore size. The δ-MnO2 @TA-PES achieved high water permeation flux of 723.9 L· m   −   2 · h   −   1 ·bar −1, excellent oil rejection with separation efficiency above 98.5% for various emulsions, and durable anti-oil-fouling performance with FRRb of 98.0%. Notably, the oil cake layer fouling on δ-MnO2 @TA-PES was greatly alleviated owing to its enhanced surface properties. In addition, δ-MnO2 @TA-PES showed high cleaning efficiency in the peroxymonosulfate (PMS) cleaning process, where the radical and nonradical pathways occurred simultaneously. And the active substances generated in the nonradical process (especially 1 O2 ) were considered as the main contributor to the reduction of irreversible fouling. Overall, the novel strategy of fouling control ensured the efficient operation of ultrafiltration membranes for the continuous oily wastewater purification. Graphic abstract: Image, graphical abstract